2008
DOI: 10.1016/j.molcel.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Translational Regulation via L11: Molecular Switches on the Ribosome Turned On and Off by Thiostrepton and Micrococcin

Abstract: The thiopeptide class of antibiotics targets the GTPase-associated center (GAC) of the ribosome to inhibit translation factor function. Using X-ray crystallography, we have determined the binding sites of thiostrepton (Thio), nosiheptide (Nosi), and micrococcin (Micro), on the Deinococcus radiodurans large ribosomal subunit. The thiopeptides, by binding within a cleft located between the ribosomal protein L11 and helices 43 and 44 of the 23S rRNA, overlap with the position of domain V of EF-G, thus explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
314
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(332 citation statements)
references
References 59 publications
15
314
0
3
Order By: Relevance
“…The individual sites for interaction with IF2, EF-Tu, EF-G, and RF3 have been mapped to the α4-loop-α5 region of purified L12 by NMR (19), and the results are consistent with the functional findings from site-directed mutagenesis (8,33). The binding of the C-terminal domain of L12 to EF-G was also detected in the ribosome•EF-G complex by cryo-EM (14,15) and in recent crystal structure data (16). Although crystal structure data are not available for the C-terminal portion of the archaeal/eukaryotic ribosomal stalk protein, some structural features have been deduced by NMR analysis of peptides that comprise the 13 C-terminal amino acids from human and Leishmania brazililiensis P1/P2 (34).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The individual sites for interaction with IF2, EF-Tu, EF-G, and RF3 have been mapped to the α4-loop-α5 region of purified L12 by NMR (19), and the results are consistent with the functional findings from site-directed mutagenesis (8,33). The binding of the C-terminal domain of L12 to EF-G was also detected in the ribosome•EF-G complex by cryo-EM (14,15) and in recent crystal structure data (16). Although crystal structure data are not available for the C-terminal portion of the archaeal/eukaryotic ribosomal stalk protein, some structural features have been deduced by NMR analysis of peptides that comprise the 13 C-terminal amino acids from human and Leishmania brazililiensis P1/P2 (34).…”
Section: Discussionsupporting
confidence: 64%
“…Kinetic experiments under saturating nucleotide conditions indicated that EF-G•GTP and EF-G•GDP bind to the ribosome with similar affinities (30). It can be inferred from current evidence that a conformational change in EF-G including the switch I region (31) occurs after GTP hydrolysis on the ribosome and induces the rearrangement of the ribosomal factorbinding center, which is composed of the sarcin/ricin loop and the L11 (E. coli terminology) binding region, including the H43/H44 domain, of the 23S/28S rRNA (15)(16)(17)32). This structural rearrangement of the factor-binding center, which depends on GTP hydrolysis, seems to be responsible for a change in the affinity of binding of the factor to the ribosome and recycling of the factor.…”
Section: Discussionmentioning
confidence: 99%
“…The "GTPase-associated center" (GAC) is responsible for recruiting translational factors and stimulating their GTPase activity. In addition to the SRL, a key component of the GAC, the other two crucial regions are the ribosomal uL10-bL12 stalk (comprised of uL10 protein and 4-6 copies of bL12) and its base comprising the uL11 region (uL11 protein and 23S rRNA helices H43 and H44) (37). Both the uL10-bL12 stalk and the uL11 region are extremely mobile elements of the ribosome.…”
Section: Resultsmentioning
confidence: 99%
“…Thiopeptides are inhibitors of protein synthesis, but their mode of action differs depending on the size of the macrocycle. Thiostrepton A ( 15 ),79 the archetypal thiopeptide, and micrococcin P1 possess 26‐membered macrocyclic cores and are known to bind to the GTPase‐associated region of the ribosome/L11 protein complex 80. Thiopeptides with 29‐membered macrocyclic cores such as GE2270 A ( 16 ), on the other hand, interact with GTP‐bound bacterial EF‐Tu, preventing the formation of the ternary complex with aa‐tRNA 81…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%